Comparing Project-Based Learning and Experiential Learning Effects on High School Students’ English Proficiency - Bindu Madewi (Cerdika: Jurnal Ilmiah Indonesia, 2026)
English proficiency remains a critical competency in global education, yet many secondary ESL classrooms still rely on teacher-centered routines that limit authentic language use. Active learning approaches such as Project-Based Learning (PBL) and Experiential Learning (EL) have been proposed as solutions, but direct comparative evidence of their effectiveness remains limited, particularly in Indonesian secondary settings. This study aims to compare the effects of PBL and EL on high school students' English proficiency using a quasi-experimental pretest-posttest design. A total of 60 ESL students at BPK Penabur School in West Java, Indonesia participated in a one-year integrated intervention combining both approaches. Quantitative data included pre- and post-assessments of overall proficiency and skill-specific performance across listening, speaking, reading, and writing, while project rubric scores and teacher perceptions provided supplementary evidence. Results showed a significant improvement in overall proficiency from a mean pretest score of 65.2 to 78.4 at posttest (p = .001), with a large effect size (Cohen's d = 0.82). Statistically significant gains were observed across all four language skills (p < .001). Teachers reported increased student engagement and willingness to communicate, while also noting time constraints and assessment workload as implementation challenges. The study concludes that integrating PBL and EL meaningfully enhances English proficiency, though sustained success requires addressing alignment and scaffolding issues in resource-constrained classrooms.